Peningkatan Kemampuan Melaksanakan Inovasi Pembelajaran Melalui Classroom Action Research (CAR) Bagi Guru-Guru SMP-Tahfidzul Qur’an Mu’adz Bin Jabal Kendari - Hunaidah, Hunaidah; Erniwati, Erniwati; Naba, Sul Daeng (Jurusan Pendidikan Fisika, 2020)
This Community Service activity intended as an effort to improve the quality of learning and professionalism of teacher in Junior High School Tahdizul Qur'an Muadz bin Jabal Kendari by using training activities to improve the ability to implement innovative learning through Classroom Action research (CAR). CAR is intended to achieve several output targets which include: 1) Increase the understanding of teacher in Junior High School Tahdizul Qur'an Muadz bin Jabal Kendari about CAR concepts and practices to maximize self-evaluation as part of the teacher professional competency development process; 2)Improve teacher understanding of CAR concepts and practices; 3) Reducing the teaching quality gap between schools partner with other schools that qualified in air-CAR for their share of problems, exchange ideas and experiences, trials with, frank discussion between a teacher and a team of science and technology, and adjustment of the solution to the institutional structures and informal practices; 4) For schools, if the teacher in Junior High School Tahdizul Qur'an Muadz bin Jabal Kendari can conduct Classroom Action Research (CAR), then student learning outcomes will improve so that it hoped that the quality of the school would also increase. At this time PKM produced seven titles of CAR proposals provided by the teacher in Junior High School Tahdizul Qur'an Muadz bin Jabal Kendari who were ready to be submitted to the Action level